The COVID-19 pandemic, psychologists’ professional quality of life and mental health - Kercher, Amy; Rahman, Jodie; Pedersen, Mangor (Frontiers in Psychology, 2024)
Background: Psychologists are at known risk of work-related stress, secondary trauma, and burnout.The COVID-19 pandemic increased stress and anxiety for communies worldwide and corresponded with an increased demand for mental health services. Our study invesgated the impact of COVID-19 on psychologists' professional quality of life, psychological symptoms and work-related stress in Aotearoa, New Zealand (NZ).Method: Ninety-nine registered psychologists were recruited via NZ professional psychology organisaons, represenng 3% of the total workforce. Survey data collected included symptoms of compassion fague and sasfacon, psychological symptoms, COVID-19-related stress and resilience, and professional and personal circumstances during the third year of the pandemic, 2022.Results: Seventy per cent reported that their work stress had increased, and 60% that their caseload intensity had increased during COVID-19. Psychologists reported receiving litle to no addional personal or professional support, while 55% reported increased personal responsibilies during the pandemic (for example, closed childcare and schools during lockdowns). High rates of compassion fague (burnout and secondary traumac stress) were reported, and low resilience. We observed that psychological distress was higher than the community averages before the pandemic and comparable with frontline healthcare professionals. Compassion fague was associated with COVID-related stress, psychological distress, years in pracce and more frequent supervision, but not with working with atrisk clients, levels of personal support or having children at home. Despite these difficules, high Compassion Sasfacon scores were also reported, with over 90% indicang they had no intenon of leaving the profession in the foreseeable future.Conclusions: Psychologists' compassion fague appears to have worsened during the COVID-19 pandemic, as have their symptoms of psychological distress. Increased workplace and clinical demands, telehealth difficules, stress relang to the pandemic, inadequate support and increased personal responsibilies were reported by psychologists. Mental health workforces are not immune to the personal and professional impacts of crises, and are at risk of burnout and secondary traumac stress. We hope that increased awareness and understanding of psychologists' own difficules during COVID-19 can be used to tackle future crises beter, and beter support mental health professionals.